PENGEMBANGAN MODEL PEMBELAJARAN ATLETIK NOMOR LEMPAR LEMBING BENTUK PERMAINAN UNTUK SISWA SEKOLAH DASAR - Syahrianursaifi, Syahrianursaifi; Musran, Musran; Kurniawan, Erizal; Yulinar, Yulinar; Husaini, Husaini (Jurnal Dedikasi Pendidikan, 2024)
This is the problem that is often overlooked by teachers who do not prepare penjasorkes learning model, causing learners are not interested in following numbers athletics javelin learning and learners will feel bored. One model of learning that can stimulate learners to participate actively in the learning process is learning models athletics javelin numbers game form. Purpose of research to the development of learning models athletics javelin number of the games for elementary school students. This type of research is the development of research. The research subject of sixth grade students of State Elementary School 8 Banda Aceh totaling 23. The instrument used in the research instrument to validate the model development. Data collection was conducted validation and reliability. The results of this study concluded that: The athletic learning model number of javelin form games for elementary school students consisting of 14 statements can be included in the learning because it has a high level of validity with the acquisition of validity score of 0.649 so that it can be used for athletic learning model javelin number game form for elementary school students and Has a level of reliability with the reliability score of 0.624 that can be used on the number of javelin shapes game play Primary School students